Small-Sided Games Training on Improving the Passing Skills of High School Futsal Players - Aldi Pratama Putra; Rachmat Kasman; Ians Aprilio (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The lack of variety in training methods often hinders the optimization of basic technical skills, particularly passing, among school-level futsal players. Scientific evidence is essential to determine the effectiveness of specific methods in significantly enhancing player performance. This study aims to: (1) determine the effect of small-sided games (SSG) training on improving the passing skills of futsal players at High School 5 Barru; (2) assess passing skill conditions without SSG training; and (3) analyze the difference in effectiveness between the experimental group and the control group. This research employed a quasi-experimental design with a pre-test and post-test. The study population consisted of all 30 futsal players at High School 5 Barru. Using a total sampling technique, the entire population was included in the study. Data was collected through passing skill tests conducted before and after the treatment period and subsequently analyzed using the t-test. The findings revealed that: (1) small-sided games training had a significant effect on improving passing skills (t_count 76.860 > t_table 2.144); (2) the control group showed no significant improvement (t_count 0.201 < t_table 2.144); and (3) a significant difference in skill enhancement existed between the two groups (t_count 17.210 > t_table 2.048). This study provides a practical contribution for coaches and physical education teachers in selecting effective training methods. Small-sided games are scientifically proven to improve technical skills within dynamic game situations, offering a superior alternative to traditional, repetitive drills.